2021
DOI: 10.1038/s41588-020-00776-w
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide meta-analysis, fine-mapping and integrative prioritization implicate new Alzheimer’s disease risk genes

Abstract: Genome-wide association studies (GWAS) have discovered numerous genomic loci associated with Alzheimer’s disease (AD), yet the causal genes and variants remain incompletely identified. We performed an updated genome-wide AD meta-analysis, which identified 37 risk loci, including novel associations near CCDC6 , TSPAN14 , NCK2 , and SPRED2 . Using three SNP-level fine-mapping methods, we identified 21 SNPs with greater th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
318
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(371 citation statements)
references
References 112 publications
(134 reference statements)
17
318
2
Order By: Relevance
“…Computational modeling and experimental analysis reveal that the substitution alters the receptor's interaction with the lipid bilayer, possibly restricting its lateral movement and favoring homo-interactions, receptor clustering and auto-activation. Constitutive activation of the EphA1 leads to aberrant downstream signaling of the small RhoGTPases, RhoA and Rac1, as previously demonstrated in several cellular and animal AD models [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionsupporting
confidence: 56%
“…Computational modeling and experimental analysis reveal that the substitution alters the receptor's interaction with the lipid bilayer, possibly restricting its lateral movement and favoring homo-interactions, receptor clustering and auto-activation. Constitutive activation of the EphA1 leads to aberrant downstream signaling of the small RhoGTPases, RhoA and Rac1, as previously demonstrated in several cellular and animal AD models [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionsupporting
confidence: 56%
“…The role of HSPGs in the prion-like spread of tau pathology has gained additional support in recent years from the analysis of tissues from the brains of patients with tauopathies and other forms of in vivo evidence. Two meta analyses of genome wide association studies for AD risk factors have implicated enhanced expression of the 3-O HS sulfotransferase gene Hs3st1 as an AD risk factor, supporting existing observations on the role of 3- O sulfated HS in tau protein uptake and phosphorylation ( Witoelar et al, 2018 ; Schwartzentruber et al, 2021 ). Consistent with in vitro work suggesting enhanced HS-tau binding promotes enhanced spread of tau pathology, Huynh et al (2019) have reported an increase in HS expression in the brains of patients with AD both in absolute terms and relative to chondroitin sulfate (CS), another member of the GAG family.…”
Section: Distinct Hs Sulfation Patterns Govern Tau-hs Interaction and Uptakesupporting
confidence: 61%
“…In contrast, significant enrichment (Bonferroni-corrected p-value < 0.05) of genes associated by common variant studies of Alzheimer's disease was identified only in microglia/macrophage cluster markers in the SNpc and striatum (Fig. 3A) 42,43 . Next, we tested for enrichment of disease risk gene expression across the 68 transcriptionally defined subpopulations (Methods).…”
Section: Enrichment Of Heritable Risk For Parkinson's Disease In the Degenerating Dopaminergic Subtypementioning
confidence: 93%
“…1B, Methods), to comprehensively profile all cell types in the SNpc. In total, we profiled 184,673 high-quality nuclei, 43.6% of which were from the NR4A2-positive cytometry gate (Methods, Fig. 1B).…”
Section: A Map Of Human Midbrain Dopaminergic Neuronsmentioning
confidence: 99%